Quantifying Leadership and Cultural Impact on Workplace Behavior: Mengukur Dampak Kepemimpinan dan Budaya pada Perilaku di Tempat Kerja - Umma, Habibatul; Firdaus, Vera (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the collective influence of change management, leadership competence, and organizational culture on the work behavior of Tanggulangin sub-district office employees. Utilizing a descriptive quantitative research approach with purposive sampling, data was gathered from 100 employees in Sidoarjo Regency, East Java. Results indicate that while change management showed no significant impact, leadership competence and organizational culture significantly influenced work behavior. These findings highlight the crucial role of effective leadership and conducive organizational cultures in shaping employee behavior, particularly in local government settings. Efforts to enhance leadership competencies and foster positive organizational cultures can greatly improve employee performance and organizational effectiveness. Highlight: Leadership Impact: Competence shapes work behavior, crucial for organizational effectiveness. Cultural Influence: Organizational culture crucially affects employee behavior, fostering productivity. Local Government Implications: Findings guide leadership and culture initiatives for enhanced performance. Keywoard: Change management, leadership competence, organizational culture, work behavior, local government.